Initial Study on Milling in an Ultrasonically Excited Metalworking Fluid Bath - Gross, Daniel; Eichinger, Miriam; Selzam, Jan Harald; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
Energy and resource efficiency are seen as key drivers of the industrial transformation towards a low carbon economy. In particular, machine tools, which are essential to value creation, have a significant share of industrial greenhouse gas emissions due to their high-energy consumption. The energy demand for the provision and supply of metalworking fluids (MWF) alone can account for up to 25% of the total energy demand. The aim of this study is to investigate and fundamentally design an alternative cooling lubricant concept. This concept does not require continuous pumping of the coolant supply. Instead, the milling operation takes place in an immersion bath filled with metalworking fluid. An additional ultrasonic (US) actuator causes the coolant to vibrate, allowing the coolant to penetrate deeper into the cutting zone. The machining tests include a comparison of classic flood cooling, immersion bath milling and immersion bath milling with US stimulation. To compare the processes, the flank wear, the workpiece surface roughness and the bending moments due to the cutting forces were analyzed. The energy assessment allows a final evaluation of the processes.
CRIS-Team Scopus Importer:2025-02-28
Keywords: energy efficiency; immersion bath; Milling; ultrasonic

Investigation of the effects of CO2 pre-cooling on the cooling capacity for cryogenic cooling in machining operations - Meier, Trixi; Selzam, Jan Harald; Röckelein, Andreas; Hanenkamp, Nico (CIRP Journal of Manufacturing Science and Technology, 2024)
Abstract: Liquid carbon dioxide (LCO2) based cryogenic cooling has shown promising results in terms of wear reduction, productivity increase and energy efficiency when machining high-temperature materials. For process-safe use with low pulsation, CO2 must be fed in the liquid state to cool the process zone. LCO2 is typically stored in riser bottles in which gaseous and liquid aggregate state coexist. A preliminary study has already shown that the liquefied state of the CO2 can be stabilized by pre-cooling. In this paper, the influence of a heat exchanger as a pre-cooling system on the cooling capacity of the CO2 is investigated and the required energy consumption is compared to unstabilized CO2, pressure increased CO2 and compressed air. It has been shown that pre-cooling leads to a more energy-efficient increase in the cooling capacity of the CO2 compared to pressure increased CO2. <br
Keywords: Cryogenic minimum quantity lubrication; Liquid carbon dioxide; Density enhancement; Cooling capacity; Machining; Energy effiency

Potentials of Optical Coherence Tomography for Process Monitoring in Laser Welding of Hairpin Windings - Baader, Marcel; Mayr, Andreas; Raffin, Tim; Selzam, Jan Harald; Kühl, Alexander; Franke, Jörg (11th International Electric Drives Production Conference (EDPC), 2021)
Optical coherence tomography (OCT) is increasingly being used to monitor and control laser-based welding processes. With the ability to provide pre-, in-, and post-process data, OCT represents a holistic sensor solution for advanced process monitoring and seam tracking. A prospective field of application is the laser welding of rectangular copper wires for so-called hairpin stators as used in electric traction motors. For each stator, a large number of high-quality contact points must be welded in a short cycle time. The quality of a weld not only depends on the laser welding process itself but also on possible manufacturing deviations from upstream process steps. Although OCT seems promising for pre-, in-, and post-process monitoring, no scientific studies exist to date concerning hairpin welding. Starting from a profound presentation of the necessary basics, this paper outlines the potentials of OCT in laser welding of hairpin windings based on first experiments. Regarding pre-process monitoring, it is shown which deviations can be detected by OCT even before the process. Analogously, the post-process monitoring feature can be used to evaluate the resulting weld shape. Further experiments explore whether in-process OCT data can be used to determine the keyhole depth during welding, providing an estimate of the welding depth. The welding of hairpins requires complex beamlines and high focus speeds, which pose high challenges to existing OCT systems. Therefore, the proof is first provided for a simplified welding task before it is performed for the hairpin use case. From the findings gained, the need for action for future research activities is derived, primarily focusing on enabling the OCT -based in-process monitoring for the hairpin welding.<br
Keywords: laser welding; optical coherence tomography; process monitoring; hairpin technology; electric motor production

Sustainable Dry Turning of Aluminum Alloys Using Pulsed High-Pressure Cryogenic Jet Cooling - Selzam, Jan Harald; Enslein, Niklas; Gross, Daniel; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
As well as producing contamination-free parts, dry machining is a sustainable alternative to conventional machining processes using metalworking fluids. Despite these benefits, chip breaking and chip removal are challenges in dry machining processes, particularly when turning ductile materials, which are known for continuous chip formation and therefore long chips. Due to their tendency to become entangled around machine components, these chips have to be removed manually, posing a risk to productivity and operator health. Recent studies have demonstrated the effectiveness of pulsed high-pressure emulsion cooling for chip breaking. This paper aims to transfer these findings to sustainable dry machining and investigates the influence of pulsed high-pressure cryogenic jet cooling on chip breaking and chip removal. Therefore, liquid CO2 at pressures up to 200 bar is used as a cooling medium in turning processes of two aluminum alloys and is applied continuously or pulsed to the machining area. It has been shown that high-pressure cryogenic jet cooling improves chip breaking and chip removal, allowing a wider range of cutting parameters, widening the process window and providing a higher level of sustainability, productivity and safety in dry machining.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Aluminum; Carbon dioxide; Dry turning; Pulsed high-pressure cryogenic jet cooling; Sustainable machining

Vibrational Microfeeding of Polymer and Metal Powders for Locally Graded Properties in Powder-Based Additive Manufacturing - Rothfelder, Richard; Lanzl, Lydia; Selzam, Jan Harald; Drummer, Dietmar; Schmidt, Michael (Journal of Materials Engineering and Performance, 2021)
Subject of this work is the contact mechanical properties and flowability of polymer and metal powders when they are dispensed on the surface of a powder bed for use in laser-based powder bed fusion in additive manufacturing. Generating local part properties in metal as well as polymer-based powder bed fusion processes is of high interest, so an approach is made to locally add additives by a vibrational microfeeding system for metal and polymer powders. To realize a controlled powder discharge, the behavior of additives, which are dropped on a surface and on a powder bed is analyzed. Influencing factors for mass flow of the powders will be excitation frequency, excitation amplitude and capillary diameter on the side of experimental setup as well as particle size distribution and physical properties on the material side.
CRIS-Team WoS Importer:2021-10-29